PENELITIAN PERUBAHAN WARNA DAN ETILEN SELAMA PEMERAMAN DAUN TEMBAKAU KULTIVAR MADURA SERTA PENGARUHNYA TERHADAP MUTU TEMBAKAU RAJANGAN - JOKO PURDIYANTO (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Colour alternation and et/tylene changes during ripening tobacco leaves cultivar Madura and its effect to the quality of slice Madura tobaccoThe colour change and elhylene production in the leaves of Madura tobacco (Nicotiana tabacum) during ripening was studied at